2017
DOI: 10.5771/0949-6181-2017-1-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of authentic leadership on the learning organization at the organizational level: The mediating role of employees’ affective commitment

Abstract: This study examines the impact of authentic leadership capabilities on the learning organization at the organizational level through employee affective commitment in Serbian organizations. Although these indirect interrelations are very important for improving the conditions for building the learning climate and culture, previous research has not usually explored them. The analysis of a survey of 502 employees in the manufacturing and service companies in the Republic of Serbia confirms these influences empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Empirical Review Keith and Smith (2019) discovered that consistency between a leader's words and actions and balanced processing are positively associated with staff engagement. The findings are consistent with the findings of Milic et al (2017) who found a significant positive relationship between balanced processing and employee affective commitment, suggesting that the authenticity of immediate superiors plays a significant role in fostering emotional attachment and identification with the organization. Bahzar (2019) demonstrated that leaders and employees in Islamic firms practiced authentic leadership and its components, including balanced processing.…”
Section: Social Exchange Theorysupporting
confidence: 90%
“…Empirical Review Keith and Smith (2019) discovered that consistency between a leader's words and actions and balanced processing are positively associated with staff engagement. The findings are consistent with the findings of Milic et al (2017) who found a significant positive relationship between balanced processing and employee affective commitment, suggesting that the authenticity of immediate superiors plays a significant role in fostering emotional attachment and identification with the organization. Bahzar (2019) demonstrated that leaders and employees in Islamic firms practiced authentic leadership and its components, including balanced processing.…”
Section: Social Exchange Theorysupporting
confidence: 90%
“…For example, Gardner et al (2005) and Kernis, (2003) have reported that the authentic leader’s behavior embodies principles and values that strive to achieve and maintain open and authentic relationships. Also, Milic et al (2017) showed that the perceptions about AL abilities moderately and positively influence employee’s AC. When employees perceive greater authenticity by the leader, they develop a stronger emotional bond.…”
Section: Research Background and Hypotheses Developmentmentioning
confidence: 96%
“…Organizational commitment has been given a solid theoretical foundation by Allen (1991, 1997) work. This concept can be defined as a psychological force that binds individuals to their organization and shapes their behavior (Meyer and Herscovitch, 2001). Allen (1991, 1997) also developed a wellaccepted model that distinguishes between three distinctive forms of commitment: affective, continuance, and normative.…”
Section: Authentic Leadership Affective Commitment and Individual Performancementioning
confidence: 99%